Rural Community Resilience: Gambir Fluctuations as Main Livelihood in Kapur IX District Nagari Koto Bangun - Irwan Irwan; Oktia Aninia Pitri; Ulfa Vitriani (JED (Jurnal Etika Demokrasi), 2022)
Gambir is the main source of livelihood for Kapur IX Nagari Koto Bangun sub-district.  This study aims to analyze the resilience of rural communities: Gambir fluctuations as the main livelihood in Nagari Koto Bangun.  This study uses a qualitative approach and data collection methods, namely in-depth interviews, non-participant observation, and document data collection.  The way to obtain informants in this research is by using proportional sampling technique.  This study shows that the process of resilience of gambier farmers in gambier price fluctuations in Nagari Koto Bangun.  This study shows that the price of gambier fluctuates which makes gambier farmers take rational actions in maintaining the economy, especially in the family.  The resilience of the gambier farming community is carried out by living frugally, opening other businesses, especially small stalls and borrowing money from gambier middlemen as an alternative to being able to rise from fluctuations in gambier as their main livelihood.Gambier fluctuations occur because of changes in the ups and downs of a variable that occurs due to market mechanisms.Changes in market mechanisms make people to take action to keep rising from Gambier fluctuations by making efforts that are rational.Novelty in this study is a rational action as an action in strengthening resilience to image fluctuations.